MENJERAT KORPORASI DALAM TINDAK PIDANA KORUPSI - Firmansyah (Madani Legal Review, 2017)
Corruption is a crucial issue that requires extraordinary handling so that it is known as one of the extra ordinary crime regime, then made a special law on the issue of Corruption and created a special agency to handle corruption in this case is the Corruption Eradication Commission which in the process of handling rarely entrenched Corporations As the Subject of Law to be held accountable. This journal aims to find out Problems related to the problems of Corporations in Corruption as well as to know the steps to ensnare Corporations in corruption. This journal uses the normative juridical method. While the analysis with descriptive method. The results of this paper is in the case of corruption is the time to ensnare the corporation, where in the case of corruption involves many corporations, because one of the goals of handling corruption is the state financial recovery (assat recovery) and The efforts to ensnare corporations as subjects in corruption cases By using L.Friedman's legal system approach that is related to the substance or rules related to the corporation must be clear and detailed, both related to the structure, that there must be communication between law enforcement officers, and the last is the legal culture that is political will from law enforcement officers.